ANEURYSMS OF THE THORACIC AORTA - Umrilloev Lutfullo Gayratovich; Sanobar Fozilovna Sirojeddinova; Aziz Bakhtiyarovich Ablyatifov (Scholars Digest Publishing, 2023)
An enlargement of the thoracic aorta ≥50% of normal size usually indicates an aneurysm (normal diameter varies according to location). Most thoracic aortic aneurysms are asymptomatic, although some patients present with chest or back pain; other symptoms and signs are usually the result of complications (eg, dissection, compression of adjacent structures, thromboembolism, rupture). The risk of rupture is proportional to the size of the aneurysm. The diagnosis is made by CT angiography or transesophageal echocardiogram (TEE). Treatment is endovascular stent grafting or surgery.
Keywords: aneurysm, thoracic aorta, aortic dissection.